The Design of Water Markets When Instream Flows Have Value - Murphy, J. J.; Dinar, A.; Howitt, R. E.; Rassenti, S. J.; Smith, V. L.; Weinberg, M. (2012)
The main objective of this paper is to design and test a decentralized exchange mechanism that generates the location-specific pricing necessary to achieve efficient allocations in the presence of instream flow values. Although a market-oriented approach has the potential to improve upon traditional command and control regulations, questions remain about how these rights-based institutions can be implemented such that the potential gains from liberalized trade can be realized. This article uses laboratory experiments to test three different water market institutions designed to incorporate instream flow values into the allocation mechanism through active participation of an environmental trader. The smart, computer-coordinated market described herein offers the potential to significantly reduce coordination problems and transaction costs associated with finding mutually beneficial trades that satisfy environmental constraints. We find that direct environmental participation in the market can achieve highly efficient and stable outcomes, although the potential does exist for the environmental agent to influence outcomes. (C) 2008 Elsevier Ltd. All rights reserved.